Frontostriatal involvement in task switching depends on genetic differences in d2 receptor density - Stelzel, Christine; Basten, Ulrike; Montag, Christian; Reuter, Martin; Fiebach, Christian (The journal of neuroscience, 2010)
Recent studies suggest an association of dopamine D2 receptor (DRD2) availability with flexibility in reward-based learning. We extend these results by demonstrating an association of genetically based differences in DRD2 density with the ability to intentionally switch between nonrewarded tasks: noncarriers of the A1 allele of the DRD2/ANKK1-TaqIa polymorphism, associated with higher DRD2 density, show increased task-switching costs, increased prefrontal switching activity in the inferior frontal junction area, and increased functional connectivity in dorsal frontostriatal circuits, relative to A1 allele carriers. A DRD2 haplotype analysis in the same sample confirmed these results, indicating an association between high D2 density and increased task-switching effort. Our results provide evidence that converges with that from association studies relating increased D2 density to deficits in cognitive flexibility in schizophrenia. We suggest that individual differences in striatal D2 signaling in healthy humans modulate goal-directed gating to prefrontal cortex, thus leading to individual differences in switching intentionally to newly relevant behaviors.
Gesehen am 28.11.2023